PENGEMBANGAN MEDIA PEMBELAJARAN BERBANTUAN KOMPUTERUNTUK PEROLEHAN KETERAMPILAN BERBICARA MAHASISWA PGSDFKIP UNTAN PONTIANAK - NIM.F25111O58, Syamsiati; Umar, H. Syahwani; Priyadi, A.Totok (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstract: deceloping instruction Media Development aspects speaking model of Learning ThroughMultimedia in improving student skill in speaking in AcademyPGSD Pontianak Graduate School Tanjungpura University,2013.This research aims to develop a model of multimedia through computer-Assisted simulation in the form of compact disc interactive material that theeligiblity aspects and aspects of media so be good and fun.interactive compact discs are sytematically designed and programmed in accordance with the curriculum.Results of this study is expected to provide theoretical and practical benefits for all parties concerned in an effort to improve outcomes in maternity speacing. Purpose of this study was to determine the develoment of interactive CDProsedure material speacking. Research mofel used is the development of research descriptive qualitative data anasis tehniques,a model adapted from Borg and Gall With the follwing steps 1) Preliminary studies, 2) Product design, 3) Design Validation, 4) Revision of the design, 5) Product trials, 6) Revision ofThe product, 7) Use of product trials, 8) Disseminationment and socialization ofThe final. Subjects tested in this study amounted to 31 people consisting of a Speaking matter experts, an instructional media experts, 3 students for field testing . Data collection is done using questionnares, interviews, Documentation Tringulation,pretest and post test, Evaluation of the program reviewed from the aspect, of learning and media aspects. Criticisms and , sutggestions are used to improve the program. Results of this study refers to 1) Product development steps. Starting From the survey , the initial product development, product testi, 2) The productOf multimedia learning computer based speaking, contain studies of endProducts , product revisions,limitation of study, 3) study results indicate that theDevelopment of multimedia learning are already using the rule development product quality assessment results of this study of matter experts and mediaexperst are very good with 4,48 and amean score 4.70. whereas the assessment results of fieid tests 4.53 creteria very well. Theresults of study showed and increasen learning wih averages obtained do pre test 5,47 and post test obtainedan average 7.47 exhaustiveness criteria for student who complete a minimum of study with percentage 86.6 Increase in score indicates that the learning program is improving student learning automes of speaking. Key Word : Development , interactive CD, treatment of speaking ABSTRAK Hj. Syamsiati, Pengembangan Media Pembelajaran Berbantuan Komputer Untuk perolehan Keterampilan Berbicara Mahasiswa PGSD FKIP Untan Pontianak,Program PascaSarjana Tehnologi Pembelajaran,Universitas Tanjungpura,2013. Penelitian ini bertujuan untuk mengembangkan model pembelajaran keterampilan berbicara dengan mengunakan multimedia berbantuan komputer dalam bentuk CD (Compact disc interactive) yang memenuhi kelayakanaspek materi dan aspek media, sehingga menjadi baik dan menyenangkan. CD Interaktif ini dirancang secara sistematis dan terprogramSesuai dengan kurikulum. Hasil penelitian ini diharapkan dapat memberikan manfaat teoritis dan praktis bagi semua pihak yang berkepentingan dalam upaya meningkatkan hasil belajar pada mata kuliah peningkatan keterampilan berbahasa. Tujuan penelitian ini adalah untuk mengetahui prosedur pengembangan CD interaktif materi ajar aspek berbicara.Model penelitian yang digunakan adalah Penelitian pengembangan yang tehnik analisis data deskriptif kualitatif yang mengadapsi dari model Brog & Gall dengan langkah langkah dalam penelitian (1) studi pendahuluan , (2) desain produk, (3) Validasi desain,(4) revisi desain, (5) uji coba produk, (6) revisi produk, (7) uji coba pemakaian ,(8) diseminasi dan sosialisasi produk akhir. Subyek ujicoba pada penelitian ini berjumlah 31 orang yang terdiri 1 orang ahli media pembelajaran, 3 orangmahasiswa untuk uji coba satu - satu, 17 0rang mahasiswa untuk uji kelompok kecil, 31 orang untuk uji coba lapangan. Pengumpulan data dilakukan dengan menggunakan dokumentasi, triagulasi, pre tes dan post test. Evaluasi terhadap program ditinjau dari aspek pembelajaran dan aspek media. Kritik dan saran digunakan untuk memperbaiki programu. Hasil penelitian mengacu pada 1) langkah pengembangan produk berangkat dari survey awal,pengembangan produk awal,uji coba produk. 2) produk multi media pembelajaran peningkatan keterampilan berbahasa berbais komputer , beriskan kajian produk akhir,revisi produk, keterbatan penelitian. 3) Hasil belajar menunjukkan bahwa pengembangan multi media pembelajaran sudah menggunakan kaidah-kaidah pengembangan. Hasil penilaian kualitas produk penelitian ini dari ahli media sangat baik dengan skor reraya 4.48 dan 4.70. Sedangkan uji lapangan 4.53,kreteria sangat baik. Hasil belajar menunjukan adanya peningkatan belajar dengan ketuntasan dengan presentase 86,6% peningkatan hasil belajar mahasiswa maha siswa PGSD. Kata kunci : Pengembangan ,CD Interaktif. Latihan aspek berbicara